Effects of a "spin doctor" in crisis communication: a serial mediation model of identification and attitudes impacting behavioral intentions. Issue 4 (8th August 2021) - Clementson, David E.
ABSTRACT: This paper combines theories of identification and image repair to explain why an organization in crisis should avoid designing messages that engage in "spin." An experiment is reported ( N = 262 nationwide U.S. Qualtrics Panel) in which a company spokesperson replies to questions from a journalist in a news interview. Results indicate that people (a) identify more with the spokesperson, and (b) have more favorable attitudes toward the business, when the spokesperson directly answers rather than spins. Serial multiple mediator modeling reveals the theoretical process of consumer behavioral intentions bolstered by an organization "coming clean" instead of spinning in a scandal.